Expected pharmacological influences related to alkaloids extracted from flavedo peel layers of citrus fruits - M. I. , Abdelgadir (International Journal of Pharmacology and Toxicology, 2023)
This study was focused at Extraction of Alkaloids from Flavedo layers of Citrus Fruits peels and its Expected Anti-Oxidant Influences on Human Health. Alkaloids have a wide range of pharmacological activities. Albedo extract was separated. Study results clearly showed the presence (p ≤ 0.05) of alkaloids in Albedo citrus peel layers compared to control. Phytochemicals are major bioactive compounds known for their health benefits. They contain significant amounts of alkaloid, which exist in edible and non-edible parts of citrus fruits.